The relationship between joint range of motion, muscular strength, and race time for sub-elite flat water kayakers - McKean, M. R.; Burkett, B. (Journal of Science and Medicine in Sport, 2010)
Upper body strength and flexibility are common training activities in elite flat water kayaking yet the relationship between joint range of motion, muscular strength, and race time is unclear. The aim of this research was to firstly quantify the flexibility and strength of sub-elite kayakers and then determine the relationship of this data to performance race times. Twenty-nine national standard kayak paddlers were assessed for shoulder and pelvic flexibility, upper body strength, and performance time. The shoulder internal and external rotation range of movement for kayak paddlers was reduced in comparison to other populations. For the female paddlers significant (p < 0.01) and strong correlations (r > 0.70) were found between shoulder flexion range of movement, shoulder strength, and strength endurance. Strength scores for kayak paddlers are reported for the first time showing the Pull:Push strength ratio for male kayak paddlers was 129%, and for females 147%. The strength ratio was significantly different (p < 0.01) across gender and also different to published ratios from other sports. Several other measures were also significantly different across gender. All paddlers showed significant and strong correlations between the three 8RM shoulder strength exercises, highlighting the importance of maintaining balance of strength for the muscles acting on the shoulder. There was only one measure, the strength endurance Bench-Pull-Max-Power for females that significantly and strongly correlated to the on-water performances; identifying the poor relationship between current dry land training activities and race performance. No single strength or ROM measure correlated strongly with on-water performances for either sex, as a sport kayaking appears to reduce the ROM about the shoulder joint.